Case reportDRESS syndrome as a complication of treatment of hepatitis C virus-associated post-inflammatory liver cirrhosis with peginterferon α2a and ribavirin - Janocha-Litwin, Justyna; Pazgan-Simon, Monika; Simon, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Various skin and systemic symptoms may develop as a complication of treatment with different medications and medicinal substances. One of them is a relatively rare drug reaction with eosinophilia and systemic symptoms, referred to as DRESS syndrome. The morphology of skin lesions and the patient’s general health can differ; the management involves withdrawal of drugs suspected of triggering DRESS syndrome, and administration of local and systemic glucocorticosteroids. In this paper we present a case of a patient with HCV associated chronic hepatitis, treated with peginterferon α2a (PEG-IFN-α2a) and ribavirin, who developed skin lesions and systemic symptoms typical of DRESS syndrome.